Author's Satisfaction in Publishing the Manual in the Journal of CV Global Health Science Group - PH, Livana; Mulyani, Sri; Indriyani, Susi (Global Health Science Group, 2023)
The publication process that is felt by each individual has several obstacles or factors delaying the publication process both from the author and from the publication services. This study aims to determine the level of author satisfaction in publishing journal manuscripts at CV Global Health. In this study using quantitative methods. The sampling technique used purposive sampling of 104 respondents. The results of the study found that the majority of respondents said they were very satisfied with the services provided by CV Global Health as many as 60 respondents (57.7%).